Egalitarian nationhoods: a political theory in defence of the voice to parliament in the Uluru Statement from the Heart. Issue 2 (3rd April 2022) - Hobbs, Harry; Jones, Benjamin T.
ABSTRACT: The 2017 Uluru Statement from the Heart called for a constitutionally enshrined Voice to parliament, and a Makarrata Commission to supervise a process of treaty-making and truth-telling. The recommendations were rejected by the Turnbull government and appear unlikely to be implemented under a Morrison government. Initially, the main objection to the Voice from government MPs was that it would upset the balance of Australia's bicameral system by creating a third chamber. Other concerns include the potential of an Indigenous Voice to divide Australians and create special privileges for a particular group. Drawing on Chaim Gans' theory of egalitarian Zionism, this article introduces the idea of egalitarian nationhoods. It argues that the Voice does not provide privilege but equality in allowing First Nations to enjoy self-determination and collective rights, something most non-Indigenous Australians take for granted.